Perceived risk, preventive behavior and enabling environment among health workers during COVID-19 pandemic in Nepal: an Online Survey - Bimala Sharma; Nirmala Shrestha; Nisha Gurung; Sanju Banstola (Journal of Gandaki Medical College, 2020)
Introduction: Perceived risk, preventive behavior and enabling environment play vital role to prevent COVID-19 transmission in health care settings. The study aimed to assess perceived risk, preventive behavior and enabling environment among healthcare workers of different cadre during COVID-19 pandemic in Nepal.